Pendampingan Pemberdayaan Masyarakat Sebagai Pendukung Ekonomi Sirkular di Lingkungan Masyarakat RW. 015 Perumahan Pondok Timur Indah Bekasi - Muhammad Khaerudin; Dwi Budi Srisulistiowati; Andy Achmad Hendharsetiawan; Kusdarnowo Hantoro; Dani Yusuf; Allan Desi Alexander (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2026)
The waste problem in Indonesia, particularly in Bekasi City, continues to worsen as the population grows and community activities increase. The conventional waste management system, which still focuses on collection and final disposal, is considered unable to address the problem optimally. Therefore, an alternative approach based on the circular economy through community empowerment is needed. This community service activity aims to increase residents' awareness and skills in RW 015 Mustikajaya Village, Bekasi City, particularly those in the Pondok Timur Indah housing area, in managing paper waste to create economically valuable creative products. The implementation method uses an Asset-Based Community Development (ABCD) approach carried out through the stages of preparation, implementation, and evaluation of activities. The program includes socialization, training in paper waste sorting, practical workshops on crafting from paper waste, and technical assistance for the community. The results of the activities show that the community has a high enthusiasm for participating in the training and can produce various creative products, such as miniature Petromax lamps and miniature Monas Monument from paper waste. In addition to improving the skills and creativity of residents, these activities also provide an understanding of the importance of a circular economy and open up business opportunities based on waste recycling. Thus, this program is expected to support the creation of a cleaner environment, increase community participation in waste management, and encourage economic independence based on waste utilization.